HASIL BELAJAR SISWA DI MI NW PANCOR KOPONG PADA MASA PANDEMI COVID-19 - Muh. Yazid; Aluh Ernawati (Program Studi PGSD Universitas Flores, 2020)
This study aims to determine student learning outcomes at MI NW Pancor Kopong during the Covid-19 pandemic. The method used in this research is descriptive qualitative to determine the extent of student learning outcomes. The population in this study were all students of MI NW Pancor Kopong, with the number of samples were Grade V. The results of this study were that the highest and lowest scores were obtained grouped according to the assessment criteria in schools, namely based on the value of the Minimum Completeness Criteria (KKM) to determine student learning outcomes of class V MI NW Pancor Kopong. The minimum completeness criteria (KKM) averaged 60. Data on learning outcomes obtained by grade V MI NW Pancor Kopong even semester students of the 2019-2020 school year were successfully obtained from UAS scores of 20 students. Quantitatively, the highest score was 80 achieved by 3 students and the lowest total score was less than 60 which was achieved by 11 students and besides that, the score was moderate.